Reconstruction Of Noe Fracture With Immediate Diced Costal Cartilage Grafting: A Case Series - Bangun, Kristaninta; Maulana, Muhammad Iqbal; Putra, Teuku Nanda (Lingkar Studi Bedah Plastik Foundation, 2018)
Background : Naso-orbital-ethmoid (NOE) fracture is one of the common injury and the management remains difficult and controversial due to the anatomic complexity. Severe facial deformity and dysfunction are the results from the untreated injury. Moreover, the results from many procedures are not aesthetically satisfying. Meanwhile diced cartilage graft popularity is increasing in order to correct nasal deformity whether post trauma, revision (secondary) rhinoplasty or cleft nose. The procedure is less time consuming, easy to perform and also highly malleable. Methods : This study presents our experience in managing four patients with NOE fracture using costal cartilage graft technique immediately after injury. A columellar V-shaped incision was made, the finely diced cartilage harvested from the eight rib was injected to the glabella, dorsum and nasal tip using one cc syringe needle with cut tip. Demographic data were obtained from the patients’ medical record. Post-operative results were observed. Result: The four surgeries were done, with average 5.75 (range, 2-9) days after injury. During the observation, nasal tip misalignment was observed in only one patient. Diced cartilage were not visible through the skin, although it could be palpable. No cartilage extrusion were occurred. After averange follow up 10.25 mo (range 8-12 mo) All patients were satisfied with their facial appearance. Conclusion: The fracture of NOE can be manage with immediate diced costal cartilage graft, since this treatment can achieve a normal facial function and appearance. The complications are low and manageable, making it as serious contender technique of choice in managing NOE fracture to other techniques. Keywords: NOE fracture, diced costal cartilage graft, facial fracture